Residual crude palm oil resources and recovery method: a review - Sulin, Siti Naderah; Mokhtar, M. N. (Malaysian Society of Agricultural Engineers, 2019)
Over the past few years, Malaysia is among countries who led the world's crude palm oil (CPO) production. This scenario however giving drawbacks due to a large volume of biomass in the form of oil palm empty fruit bunches (OPEFB), oil palm mesocarp fiber (OPMS), decanter cake (DC) and palm oil mill effluent (POME). Whilst they still contain valuable residual oil, which currently million tons of these biomass treated as solid and liquid waste. As opposed to the elimination approach, this review paper is aimed to give an overview on the residual crude palm oil recovery method from different types of biomass resources. Common method proposed in the industry is by extraction using an organic solvent such as n-hexane, but due to it classified as hazardous to air pollutant and highly flammable, many researchers tried to find better approaches such as green solvent D-limonene, sub-critical water, and supercritical CO2 with or without ethanol. Apart from that, some of the researchers recovered the residual oil by physical means such as pressing, hydro solvent-assisted steam extraction (HYSASE), high pressure water spray (HPWS) and nanofiber absorption technique. For the time being, most of the researchers focused on the oil recovery for a specific type of biomass, but by understanding the method principle, it could bring possibility to treat another type of biomass or can be combined to get high yield of residual oil. Therefore, this strategy will pave the way for several potentials in residual oil utilization such as biodiesel, bio-lubricant, MAG and DAG productions.